Evaluation and management of pressure ulcers in plastic surgery department at tertiary care center in India - Sinwar, Prabhu Dayal; Jain, Rakesh Kumar; Kalra, Sushrut; Sharma, Rahul (International Surgery Journal, 2024)
Background: A pressure ulcer also known as decubitus ulcers, bedsores, or pressure sores is a localized injury to the skin and/ or underlying tissue usually over a bony prominence, as a result of unrelieved pressure or pressure in combination with shear. When extrinsic pressure exceeds the capillary pressure of 32 mmHg than vessel occluded and blood flow stops. When pressure not relieved for 5 minute every 2 hour, then necrosis and ulceration will result. Methods: Retrospective study of 74 patients with pressure injury admitted in SMS hospital Jaipur during 3 year duration from September 2019 to August 2022 requiring plastic surgery intervention. Patient specific factor, wound characteristics and flap outcomes analysed in study. Results: Patients with early-stage pressure injury (stage I and II) and advance stage (stage III and IV) with deteriorating or terminal co-morbidities, managed with conservative treatment in form of dressing with pressure management. Patients with advance stage pressure injury (stage III and IV) managed with active operative intervention in form of debridement and flap cover surgery. Conclusions: Prevention of pressure ulcer development is mainstay in management of both development and recurrence of pressure ulcer.